2010
DOI: 10.4103/0019-5359.94406
|View full text |Cite
|
Sign up to set email alerts
|

Steroid responsive prolonged thrombocytopenia in dengue

Abstract: Prolonged thrombocytopenia in a usual case of dengue virus infection is uncommon. Dengue-related thrombocytopenia is self-limiting and responds within 3-5 days. An underlying immunological disorder may be responsible for delayed return of platelet count to a normal level. We present a case of prolonged thrombocytopenia in a case of dengue hemorrhagic fever. The response to steroids suggests a possible immunological dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Thrombocytopenia was a consistent feature of DF and almost always found in DHF/SS, and usually, platelet count normalizes by day 10 of fever. Very few cases were reported worldwide having prolonged thrombocytopenia beyond day 10 . Dengue HLH should be suspected in any patient with persistent thrombocytopenia who has a history of fever in recent past.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thrombocytopenia was a consistent feature of DF and almost always found in DHF/SS, and usually, platelet count normalizes by day 10 of fever. Very few cases were reported worldwide having prolonged thrombocytopenia beyond day 10 . Dengue HLH should be suspected in any patient with persistent thrombocytopenia who has a history of fever in recent past.…”
Section: Discussionmentioning
confidence: 99%
“…Very few cases were reported worldwide having prolonged thrombocytopenia beyond day 10. 44,46 Dengue HLH should be suspected in any patient with persistent thrombocytopenia who has a history of fever in recent past.…”
Section: Discussionmentioning
confidence: 99%
“…17 Bhalla et al reported a 34-year-old woman who had persistent thrombocytopenia for more than 10 days with bleeding manifestations and responded well to steroids. 18 Luiz Jose'de Souza et al has reported a 46-year-old woman with a dengue virus infection with prolonged ITP which responded to steroids. 19…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, as it may hold true for most diseases, a high index of suspicion and a search for certain clinical indicators may be the only approach to diagnosing such a predicament. To the best of our knowledge, only a few authors in the past have reported an association with dengue and ITP, all having a dramatic response with corticosteroids [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%